A Solution to VRPTW Based on Improved GA-AMMAS Algorithm. Issue 3 (April 2020) - Han, Ming; Wang, Ya-Bin
Abstract: Vehicle routing problem with time windows (VRPTW) is a NP difficult problem, and it has important applications in military logistics, especially the distribution of wartime military equipment, materials and spare parts. In the last decade, numerous new methods for VRPTW have sprung up. However, few researches have been made in the study of VRPTW of wartime distribution. Hence, a two-stage solution is proposed in this paper to solve the VRPTW in complex dynamic environment during the war. That is, static route optimization in the pre-planning stage and dynamic route re-planning in the execution stage for sudden or changing enemy threats. An improved hybrid algorithm of Genetic algorithm and adaptive maximum-minimum ant system (GA-AMMAS) is designed in this paper for the solution of the model above.